The journal of Jesse Smoke : a Cherokee boy - Bruchac, Joseph, 1942- (My name is America., 2001)
Jesse Smoke, a sixteen-year-old Cherokee, begins a journal in 1837 to record stories of his people and their difficulties as they face removal along the Trail of Tears. Includes a historical note giving details of the removal.